Hormone therapy for diffuse mastopathy - I. V. Vysotskaya; V. P. Letyagin; N. V. Levkina (Опухоли женской репродуктивной системы, 2014)
The paper considers the issues of hormone therapy for diffuse fibrocystic mastopathy concurrent with different hormonal homeostatic disorders and gynecological diseases.